A confusing Case – Weissella confusa Prosthetic Joint Infection: A Case Report and Review of the Literature. Issue 3 (2014) - Medford, Richard; Patel, Samir N; Evans, Gerald A
Abstract : The authors describe the first case of Weissella confusa infection of a prosthetic joint. Identification of the pathogen required 16S ribosomal RNA sequencing of isolates obtained on two separate occasions during the assessment of an elderly woman with a painful, swollen knee following total knee arthroplasty. A review of reported human infections due to W confusa are summarized, and risk factors and pitfalls in the application of empirical antimicrobial therapy pending definitive microbiological identification are discussed.